Prostate Biopsy: Targeting Cancer for Detection and Therapy - Taneja, Samir S (MedReviews, LLC, 2006)
Despite improvements in cancer detection, prostate biopsy still lacks the ability to accurately map locations of cancer within the prostate. Improvements in prostate imaging may allow more accurate mapping of overall disease volume. Magnetic resonance (MR) spectroscopy allows improved specificity in detecting even small foci of disease within the peripheral zone. Improvements in MR-guided biopsy techniques may allow this technology to be adapted to therapeutics as well. Computer modeling of individual prostates serves as a means of designing optimized plans for prostate biopsy. The use of novel targeted biopsy schemes may allow an integration of available technologies in detection and localization of prostate cancer. Computer-directed needle biopsies based on anatomic landmarks within the prostate and computerized three-dimensional reconstruction of the gland may allow a highly reproducible means of identifying small foci of cancer, targeting them for therapy, and monitoring for recurrence. The TargetScan® system (Envisioneering Medical Technologies, St. Louis, MO) is the first technology to integrate available targeting methodologies in a systematic fashion.